Method for preparing high-strength beta titanium alloy with two-phase mixed ultra-fine grain structure through medium-temperature constant-load deformation
Through the medium-temperature constant load deformation process combined with high-temperature forging and heat treatment, the limitations of high-strength β-titanium alloy heat treatment and thermal machining methods were solved, and the mixed ultrafine crystal structure of α-phase and β-phase with excellent mechanical properties was successfully prepared, achieving high-quality Improved strength and plasticity, while simplifying the process flow and reducing energy consumption.
Patent Information
- Application Number
- CN202411316320.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing heat treatment and thermal machining methods of high-strength β-titanium alloys are difficult to effectively refine grains, resulting in poor strength-toughness matching, complex process and high energy consumption, making it difficult to prepare ultrafine crystal structures with excellent mechanical properties.
Using a medium-temperature and constant load deformation process, combined with the pre-mounted high-temperature forging and heat treatment process, the transition temperature of the α-phase and β-phase of the alloy is controlled by smelting of vacuum consumable electrodes and multiple forgings, and the conversion temperature of the α-phase and β-phase of the alloy is applied to compress and deform, and finally obtained with High-strength β-titanium alloy with ultrafine crystal structure mixed with α-phase and β-phase.
It has achieved the reduction of internal defects of the alloy, improved the uniformity and density of the structure, achieved high strength and excellent plastic properties, and has simple process and strong controllability, reducing energy loss and production cycle.
Smart Images

Figure CN119194139A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-strength titanium alloys, in particular to a medium-temperature constant-load deformation method for preparing a high-strength β titanium alloy with an ultrafine grain structure mixed with α and β phases. Background Art
[0002] Titanium and titanium alloys are widely used in aerospace, biomedicine, petrochemical, marine and other fields due to their excellent properties. Among them, high-strength β-titanium alloys have attracted much attention due to their excellent mechanical properties such as high specific strength, corrosion resistance, suitable strength and toughness combination, and good hardenability. They can replace some high-strength steel structural parts, such as aircraft landing gear or fasteners, and reduce the weight of structural parts by 30% to 40%. With the development of technology, people's requirements for materials are getting higher and higher, which has prompted the research on high-strength β-titanium alloys with higher strength and better plasticity.
[0003] The common method to improve the performance of high-strength β titanium alloy is to control the alloy structure, which can be achieved in many ways, such as heat treatment and thermomechanical processing. Heat treatment can significantly improve the alloy structure, and aging treatment in heat treatment can significantly strengthen the alloy; in actual production processes, it is often necessary to go through thermomechanical processing such as forging and rolling, which can reduce alloy defects, improve alloy density, and significantly refine the structure. However, both methods have their limitations. The degree of grain refinement of heat treatment methods is limited, and it is difficult to ensure a good match between strength and toughness; and mechanical hot working methods are difficult to determine due to the narrow hot working range and high sensitivity to hot working processes of high-strength β titanium alloys. The microstructure morphology before hot working, hot working temperature and hot working method will affect the morphology, distribution, size, etc. of α phase and β phase. Unreasonable process design will not only fail to significantly improve the alloy performance, but may even cause a sharp deterioration in performance. The preparation of fine-grained materials and even ultra-fine-grained materials is a very effective means to improve the performance of alloys. Fine grain strengthening can simultaneously improve the strength and plasticity of materials, but it often has high requirements in production processes and consumes a lot of energy. Summary of the invention
[0004] In order to solve the technical problem of casting defects in alloys, the present invention provides a method for preparing a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation.
[0005] The present invention is a medium temperature constant load deformation processing and forming process, combined with the previous high temperature forging process and heat treatment process, which can effectively reduce the internal defects of the alloy, regulate the alloy structure, and finally prepare an alloy with an ultrafine grain structure. This new method is easy to operate and has strong controllability, which is of great significance for the application and promotion of high-strength β titanium alloy.
[0006] A method for preparing a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation is specifically carried out in the following steps:
[0007] 1. Weigh titanium sponge, high purity aluminum, high purity chromium, high purity tin, aluminum-molybdenum alloy, aluminum-vanadium alloy and iron nails as raw materials according to the atomic percentage: Al is 2.5% to 4.5%, Mo is 4% to 7%, V is 4.5% to 7.5%, Cr is 2.5% to 4.5%, Sn is 1.5% to 3.5%, Fe is 0.3% to 1.0% and the balance is Ti;
[0008] 2. Cleaning the raw material obtained in step 1, pressing it into multiple electrodes, then welding them into consumable electrodes, and then using a vacuum consumable electrode smelting process to prepare an alloy ingot through two smelting processes;
[0009] The α / β phase transition temperature of the alloy ingot was determined by metallographic method as T β ;
[0010] 3. Cutting off the surface of the alloy ingot obtained in step 2 to remove the oil stain, and then coating the surface with an anti-oxidation coating; heating the alloy ingot at a temperature of (T β +150℃)~(T β +200℃) for 110min to 140min, then forge the blank to make a forged blank, and then air cool the forged blank to room temperature; then heat the blank at a temperature of (T β +30℃)~(T β +80℃) for 90min~120min, then forge for the second time, and cool to room temperature with the furnace; β -80℃)~(T β -20℃) for 80min~100min, then forge for the third time, and cool to room temperature with the furnace; β -80℃)~(T β -20℃) for 80min~100min, then forge for the fourth time, and cool to room temperature with the furnace; β -100℃)~(T β -20℃) for 80min to 100min, and then fine forging is performed to obtain a forged high-strength β titanium alloy; at this time, the forged high-strength β titanium alloy has a uniform structure and casting defects are basically eliminated;
[0011] 4. Cut the forged high-strength β titanium alloy obtained in step 3 to obtain a heat-treated piece, and set the heat treatment furnace temperature to (T β +20℃)~(T β+40℃), after the temperature in the furnace rises to the preset temperature, the heat-treated part is placed in the heat-treatment furnace, kept warm for 50min to 120min, and then air-cooled to room temperature; at this time, the microstructure of the forged high-strength β titanium alloy is a single β phase, and the alloy grain size is coarse;
[0012] 5. Process the heat-treated parts after the heat treatment in step 4 into several deformed parts, and use an electronic creep endurance testing machine to perform the deformation process. Place the deformed parts at the exact center of the pressure head of the testing machine, return the stress to zero, adjust the pressure head height, and then apply a preload pressure of 20MPa~50MPa to fix the deformed parts. Then, fix a thermocouple at the upper pressure head, the lower pressure head and the middle of the two pressure heads of the testing machine, respectively. Then, close the insulation furnace of the testing machine, set the target deformation temperature to 600℃~650℃, the target load to 450MPa~550MPa, and then heat the insulation furnace at a heating rate of 15~20℃ / min. After reaching the target temperature, start insulation for 20~50min, and then load to the target load at a load increase rate of 5~8MPa / s. Maintain a constant load for compression. After the compression is completed, unload the load within 3s~5s, cool to room temperature with the furnace, and obtain a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure.
[0013] The alloy exhibited excellent deformation ability during the entire deformation process in step five; the workpiece removed was in the shape of a round pancake with no cracks on the surface or inside. The deformed structure was an ultrafine grain structure mixed with α and β phases, and the grain size was generally less than 1 μm.
[0014] The invention defines the composition of high-strength β-titanium alloy, and prepares the cast high-strength β-titanium alloy by vacuum consumable electrode melting technology; the cast high-strength β-titanium alloy is subjected to five-time high-temperature forging treatment to obtain the forged high-strength β-titanium alloy, the purpose of which is to eliminate the casting defects in the cast alloy, improve the density of the alloy, and improve the performance of the final alloy; then the forged high-strength β-titanium alloy is subjected to single-phase solid solution heat treatment, which not only obtains the alloy structure required before deformation, but also eliminates the internal stress generated by forging, which is conducive to the next deformation; the heat-treated high-strength β-titanium alloy is subjected to constant load deformation at medium temperature, and is cooled with the furnace after the deformation, and the obtained high-strength β-titanium alloy has an ultrafine grain structure mixed with α phase and β phase, and the grain size is generally less than 1μm, which will make the alloy have excellent plasticity and extremely high strength. In addition, there are no cracks inside and outside the alloy, showing excellent deformation performance. Compared with conventional thermal mechanical processing methods for high-strength β titanium alloys, the present invention can not only obtain a two-phase mixed ultrafine grain structure, but also make full use of energy, reduce energy loss, and improve production controllability, which is simple and easy to operate. This method further expands the thermal processing technology of high-strength β titanium alloys, reduces production requirements, and the obtained two-phase mixed ultrafine grain titanium alloy has excellent mechanical properties, which is of great significance for further improving the performance of high-strength β titanium alloys and further promoting alloy application scenarios.
[0015] Beneficial effects of the present invention:
[0016] (1) The present invention achieves compression deformation of the alloy at medium temperature through pre-control of the alloy structure, and also obtains an ultrafine grain structure of mixed α phase and β phase. This method further expands the hot working process of high-strength β titanium alloy, reduces production requirements, and greatly shortens the production cycle. At the same time, the obtained two-phase mixed ultrafine grain titanium alloy will have excellent mechanical properties, with a strength of more than 1700MPa at room temperature and an elongation of not less than 7%, which is of great significance for further improving the performance of high-strength β titanium alloy and further promoting the application scenarios of alloys.
[0017] (2) The deformation temperature of the present invention is controlled at a medium temperature, which not only obtains a two-phase mixed structure, but also reduces energy loss while achieving a smooth deformation process. In addition, the furnace cooling process after the deformation can further stabilize the alloy structure, reduce residual stress, and achieve full utilization of energy.
[0018] (3) The medium-temperature constant load deformation method for preparing a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure proposed in the present invention has a simple process, strong overall controllability, and a short processing cycle, which is conducive to the large-scale application of high-strength β titanium alloy.
[0019] The invention prepares a high-strength beta titanium alloy with a two-phase mixed ultrafine grain structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 FIG. 1 is a scanning electron microscope image of a forged high-strength β titanium alloy after five-time high-temperature forging treatment in step 3 of Example 1; FIG. b is a high-magnification image of the white box area in FIG. a;
[0021] Figure 2 This is a scanning electron microscope image of the heat-treated part after the treatment in step 4 of Example 1, and Figure b is a high-magnification image of the white box area in Figure a;
[0022] Figure 3 The microstructure images of the high-strength β titanium alloy with a two-phase mixed ultrafine grain structure obtained in Example 1; Figure a is a scanning electron microscope image, Figure b is an electron backscatter diffraction image, Figure c is a transmission electron microscope image, and Figure d is an enlarged transmission electron microscope image;
[0023] Figure 4 The microstructure images of the high-strength β titanium alloy with a two-phase mixed ultrafine grain structure obtained in Example 2; Figure a is a scanning electron microscope image, and Figure b is an electron backscatter diffraction image. DETAILED DESCRIPTION
[0024] Specific implementation method 1: This implementation method is a method for preparing a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure by medium temperature constant load deformation, which is specifically carried out in the following steps:
[0025] 1. Weigh titanium sponge, high purity aluminum, high purity chromium, high purity tin, aluminum-molybdenum alloy, aluminum-vanadium alloy and iron nails as raw materials according to the atomic percentage: Al is 2.5% to 4.5%, Mo is 4% to 7%, V is 4.5% to 7.5%, Cr is 2.5% to 4.5%, Sn is 1.5% to 3.5%, Fe is 0.3% to 1.0% and the balance is Ti;
[0026] 2. Cleaning the raw material obtained in step 1, pressing it into multiple electrodes, then welding them into consumable electrodes, and then using a vacuum consumable electrode smelting process to prepare an alloy ingot through two smelting processes;
[0027] The α / β phase transition temperature of the alloy ingot was determined by metallographic method as T β ;
[0028] 3. Cutting off the surface of the alloy ingot obtained in step 2 to remove the oil stain, and then coating the surface with an anti-oxidation coating; heating the alloy ingot at a temperature of (T β +150℃)~(T β +200℃) for 110min to 140min, then forge the blank to make a forged blank, and then air cool the forged blank to room temperature; then heat the blank at a temperature of (T β+30℃)~(T β +80℃) for 90min~120min, then forge for the second time, and cool to room temperature with the furnace; β -80℃)~(T β -20℃) for 80min~100min, then forge for the third time, and cool to room temperature with the furnace; β -80℃)~(T β -20℃) for 80min~100min, then forge for the fourth time, and cool to room temperature with the furnace; β -100℃)~(T β -20℃) for 80min to 100min, and then fine forging is performed to obtain a forged high-strength β titanium alloy;
[0029] 4. Cut the forged high-strength β titanium alloy obtained in step 3 to obtain a heat-treated piece, and set the heat treatment furnace temperature to (T β +20℃)~(T β +40℃), after the temperature in the furnace rises to the preset temperature, put the heat-treated parts into the heat-treatment furnace, keep the temperature for 50min to 120min, and then air-cool to room temperature;
[0030] 5. Process the heat-treated parts after the heat treatment in step 4 into several deformed parts, and use an electronic creep endurance testing machine to perform the deformation process. Place the deformed parts at the exact center of the pressure head of the testing machine, return the stress to zero, adjust the pressure head height, and then apply a preload pressure of 20MPa~50MPa to fix the deformed parts. Then, fix a thermocouple at the upper pressure head, the lower pressure head and the middle of the two pressure heads of the testing machine, respectively. Then, close the insulation furnace of the testing machine, set the target deformation temperature to 600℃~650℃, the target load to 450MPa~550MPa, and then heat the insulation furnace at a heating rate of 15~20℃ / min. After reaching the target temperature, start insulation for 20~50min, and then load to the target load at a load increase rate of 5~8MPa / s. Maintain a constant load for compression. After the compression is completed, unload the load within 3s~5s, cool to room temperature with the furnace, and obtain a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure.
[0031] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: in step 1, the mass purity of the titanium sponge is 99%, the mass purity of the high-purity aluminum is 99%, the mass purity of the high-purity chromium is 99.9%, the mass purity of the high-purity tin is 99%, the molybdenum content in the aluminum-molybdenum alloy is 50.5wt.%, and the vanadium content in the aluminum-vanadium alloy is 47.44wt.%. The rest is the same as specific embodiment 1.
[0032] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: when weighing in step 1, 1-3% of the mass of Al element and 4-7% of the mass of Sn element are added to compensate for the burning loss during the smelting process. The rest is the same as specific implementation method 1 or 2.
[0033] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 2, the raw material is ultrasonically cleaned with anhydrous ethanol. The rest is the same as specific embodiments 1 to 3.
[0034] Specific implementation mode 5: This implementation mode is different from specific implementation modes 1 to 4 in that the anti-oxidation coating in step 3 is TB1030 glass powder. The rest is the same as specific implementation modes 1 to 4.
[0035] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that step 4 is performed using a resistance heat treatment furnace. The rest is the same as specific implementation methods 1 to 5.
[0036] Specific implementation method 7: This implementation method is different from specific implementation methods 1 to 6 in that the material of the pressure head used in step 5 is nickel-based high-temperature alloy. The rest is the same as specific implementation methods 1 to 6.
[0037] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: Step 5 monitors the temperature change in the compression process in real time through a thermocouple to control the temperature fluctuation in the compression process to be less than ±10° C. The rest is the same as specific embodiments 1 to 7.
[0038] Specific implementation method 9: This implementation method is different from specific implementation methods 1 to 8 in that the compression amount in step 5 is controlled to be 50% to 80%. The rest is the same as specific implementation methods 1 to 8.
[0039] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the high-strength β titanium alloy with a two-phase mixed ultrafine grain structure obtained in step 5 has an ultrafine grain structure mixed with α phase and β phase, and the grain size is less than 1 μm. Other aspects are the same as specific embodiments 1 to 9.
[0040] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.
[0041] Embodiment 1:
[0042] A method for preparing a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation is specifically carried out in the following steps:
[0043] 1. According to the atomic percentage: Al is 3.5%, Mo is 5%, V is 6%, Cr is 3%, Sn is 2%, Fe is 0.5% and the balance is Ti, sponge titanium (purity>99%), high purity aluminum (purity>99%), high purity chromium (purity>99.9%), high purity tin (purity>99%), aluminum-molybdenum alloy (Mo content 50.5wt.%), aluminum-vanadium alloy (V content 47.44wt.%) and iron nails are weighed as raw materials;
[0044] 2. The raw material obtained in step 1 is ultrasonically cleaned with anhydrous ethanol, pressed into multiple electrodes, and then welded into consumable electrodes, and then smelted twice using a vacuum consumable electrode smelting process to obtain an alloy ingot;
[0045] The α / β phase transition temperature T of the alloy ingot was determined by metallographic method. β 815℃;
[0046] 3. Cut off the surface of the alloy ingot obtained in step 2 to remove oil stains, and then apply an anti-oxidation coating on the surface; keep the alloy ingot at a temperature of 980°C for 120 minutes, then forge it to make a forged billet, and then air-cool the forged billet to room temperature; then keep it at a temperature of 870°C for 100 minutes, then forge it for the second time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the third time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the fourth time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the fourth time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the fourth time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then perform fine forging, and obtain a forged high-strength β titanium alloy;
[0047] 4. Cut the forged high-strength β titanium alloy obtained in step 3 to obtain a heat-treated piece, set the temperature of the heat treatment furnace to 840°C, and after the temperature in the furnace rises to a preset temperature, put the heat-treated piece into the heat treatment furnace, keep it warm for 60 minutes, and then air-cool it to room temperature;
[0048] 5. Process the heat-treated parts after the heat treatment in step 4 into several deformed parts with a size of Ф6mm×9mm. Use RDL-50 electronic creep endurance testing machine for deformation process. The material of the indenter used is nickel-based high-temperature alloy. Place the deformed workpiece at the center of the indenter of the testing machine, return the stress to zero, adjust the indenter height, and then apply a preload pressure of 20MPa to fix the deformed workpiece. Then, fix a thermocouple on the upper indenter, the lower indenter and the middle of the two indenters of the testing machine respectively. Use the thermocouple to monitor the temperature change in the compression process in real time, and control the temperature fluctuation of the compression process to be less than ±10℃. Then, the holding furnace of the testing machine was closed, and the target deformation temperature and the target load were set to 600°C and 500MPa, and the temperature in the holding furnace was increased at a rate of 15°C / min. After reaching the target temperature, the temperature was kept warm for 30 minutes, and then the load was increased at a rate of 6MPa / s to the target load. The load was kept constant for compression with a compression amount of 55% to 60%. After the compression was completed, the load was removed within 3s and the alloy was cooled to room temperature with the furnace to obtain a high-strength β titanium alloy (Ti-3.5Al-5Mo-6V-3Cr-2Sn-0.5Fe) with a two-phase mixed ultrafine grain structure.
[0049] Figure 1 Figure 1 is a scanning electron microscope image of the forged high-strength β titanium alloy after five-time high-temperature forging treatment in step 3 of Example 1; Figure b is a high-magnification image of the white box area in Figure a. As can be seen from the figure, the structure of the forged high-strength β titanium alloy consists of β grains, continuous grain boundary α (α GB ) phase and a small amount of fine secondary α(α s ) phase, and the β grains are obviously flattened, and the length direction is obviously larger than the height direction. According to the measurement, the grain length is generally greater than 50μm.
[0050] Figure 2 Figure 1 is a scanning electron microscope image of the heat-treated part after step 4 of Example 1, and Figure b is a high-magnification image of the white box area in Figure a. It can be found that after solution treatment, the alloy structure becomes a single β phase, and the grain size is significantly increased. After calculation, the average size is about 75.1μm.
[0051] Figure 3 The microstructure images of the high-strength β titanium alloy with a two-phase mixed ultrafine grain structure obtained in Example 1 are shown in Figure a, Figure b is an electron backscatter diffraction image, Figure c is a transmission electron microscope image, and Figure d is an enlarged transmission electron microscope image. It can be found that after deformation, the alloy structure changes to α phase and β phase, and the grains are greatly refined. After calculation, the average grain size is 0.47μm.
[0052] Embodiment 2:
[0053] A method for preparing a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation is specifically carried out in the following steps:
[0054] 1. According to the atomic percentage: Al is 3.5%, Mo is 5%, V is 6%, Cr is 3%, Sn is 2%, Fe is 0.5% and the balance is Ti, sponge titanium (purity>99%), high purity aluminum (purity>99%), high purity chromium (purity>99.9%), high purity tin (purity>99%), aluminum-molybdenum alloy (Mo content 50.5wt.%), aluminum-vanadium alloy (V content 47.44wt.%) and iron nails are weighed as raw materials;
[0055] 2. The raw material obtained in step 1 is ultrasonically cleaned with anhydrous ethanol, pressed into multiple electrodes, and then welded into consumable electrodes, and then smelted twice using a vacuum consumable electrode smelting process to obtain an alloy ingot;
[0056] The α / β phase transition temperature T of the alloy ingot was determined by metallographic method. β 815℃;
[0057] 3. Cut off the surface of the alloy ingot obtained in step 2 to remove oil stains, and then apply an anti-oxidation coating on the surface; keep the alloy ingot at a temperature of 980°C for 120 minutes, then forge it to make a forged billet, and then air-cool the forged billet to room temperature; then keep it at a temperature of 870°C for 100 minutes, then forge it for the second time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the third time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the fourth time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the fourth time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then forge it for the fourth time, and cool it to room temperature with the furnace; keep it at a temperature of 780°C for 90 minutes, then perform fine forging, and obtain a forged high-strength β titanium alloy;
[0058] 4. Cut the forged high-strength β titanium alloy obtained in step 3 to obtain a heat-treated piece, set the temperature of the heat treatment furnace to 840°C, and after the temperature in the furnace rises to a preset temperature, put the heat-treated piece into the heat treatment furnace, keep it warm for 60 minutes, and then air-cool it to room temperature;
[0059] 5. Process the heat-treated parts after the heat treatment in step 4 into several deformed parts with a size of Ф6mm×9mm. Use RDL-50 electronic creep endurance testing machine for deformation process. The material of the indenter used is nickel-based high-temperature alloy. Place the deformed workpiece at the center of the indenter of the testing machine, return the stress to zero, adjust the indenter height, and then apply a preload pressure of 20MPa to fix the deformed workpiece. Then, fix a thermocouple on the upper indenter, the lower indenter and the middle of the two indenters of the testing machine respectively. Use the thermocouple to monitor the temperature change in the compression process in real time, and control the temperature fluctuation of the compression process to be less than ±10℃. Then, the holding furnace of the testing machine was closed, and the target deformation temperature and the target load were set to 650°C and 500MPa, and the temperature in the holding furnace was increased at a rate of 15°C / min. After reaching the target temperature, the temperature was kept warm for 30 minutes, and then the load was increased at a rate of 6MPa / s to the target load. The load was kept constant for compression, and the compression amount was 75% to 80%. After the compression was completed, the load was removed within 3s and the alloy was cooled to room temperature with the furnace to obtain a high-strength β titanium alloy (Ti-3.5Al-5Mo-6V-3Cr-2Sn-0.5Fe) with a two-phase mixed ultrafine grain structure.
[0060] Figure 4 The microstructure images of the high-strength β titanium alloy with a two-phase mixed ultrafine grain structure obtained in Example 2 are shown in Figure a, and Figure b is an electron backscatter diffraction image. It can be found that after deformation, the alloy structure changes to α phase and β phase, and the grains are greatly refined. After calculation, the average grain size is 0.64μm.
Claims
1. A method for preparing a high-strength β-titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation, characterized in that The method is specifically carried out in the following steps:
1. Weigh titanium sponge, high purity aluminum, high purity chromium, high purity tin, aluminum-molybdenum alloy, aluminum-vanadium alloy and iron nails as raw materials according to the atomic percentage: Al is 2.5% to 4.5%, Mo is 4% to 7%, V is 4.5% to 7.5%, Cr is 2.5% to 4.5%, Sn is 1.5% to 3.5%, Fe is 0.3% to 1.0% and the balance is Ti; 2. Cleaning the raw material obtained in step 1, pressing it into multiple electrodes, then welding them into consumable electrodes, and then using a vacuum consumable electrode smelting process to prepare an alloy ingot through two smelting processes; The α / β phase transition temperature of the alloy ingot was determined by metallographic method as T β ; 3. Cutting off the surface of the alloy ingot obtained in step 2 to remove the oil stain, and then coating the surface with an anti-oxidation coating; heating the alloy ingot at a temperature of (T β +150℃)~(T β +200℃) for 110min to 140min, then forge the blank to make a forged blank, and then air cool the forged blank to room temperature; then heat the blank at a temperature of (T β +30℃)~(T β +80℃) for 90min~120min, then forge for the second time, and cool to room temperature with the furnace; β -80℃)~(T β -20℃) for 80min~100min, then forge for the third time, and cool to room temperature with the furnace; β -80℃)~(T β -20℃) for 80min~100min, then forge for the fourth time, and cool to room temperature with the furnace; β -100℃)~(T β -20℃) for 80min to 100min, and then fine forging is performed to obtain a forged high-strength β titanium alloy; 4. Cut the forged high-strength β titanium alloy obtained in step 3 to obtain a heat-treated piece, and set the heat treatment furnace temperature to (T β +20℃)~(T β +40℃), after the temperature in the furnace rises to the preset temperature, put the heat-treated parts into the heat-treatment furnace, keep the temperature for 50min to 120min, and then air-cool to room temperature; 5. Process the heat-treated parts after the heat treatment in step 4 into several deformed parts, and use an electronic creep endurance testing machine to perform the deformation process. Place the deformed parts at the exact center of the pressure head of the testing machine, return the stress to zero, adjust the pressure head height, and then apply a preload pressure of 20MPa~50MPa to fix the deformed parts. Then, fix a thermocouple at the upper pressure head, the lower pressure head and the middle of the two pressure heads of the testing machine, respectively. Then, close the insulation furnace of the testing machine, set the target deformation temperature to 600℃~650℃, the target load to 450MPa~550MPa, and then heat the insulation furnace at a heating rate of 15~20℃ / min. After reaching the target temperature, start insulation for 20~50min, and then load to the target load at a load increase rate of 5~8MPa / s. Maintain a constant load for compression. After the compression is completed, unload the load within 3s~5s, cool to room temperature with the furnace, and obtain a high-strength β titanium alloy with a two-phase mixed ultrafine grain structure.
2. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that In step 1, the mass purity of the sponge titanium is 99%, the mass purity of the high-purity aluminum is 99%, the mass purity of the high-purity chromium is 99.9%, the mass purity of the high-purity tin is 99%, the molybdenum content in the aluminum-molybdenum alloy is 50.5wt.%, and the vanadium content in the aluminum-vanadium alloy is 47.44wt.%.
3. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that In step 1, when weighing, the mass of Al element is increased by 1-3%, and the mass of Sn element is increased by 4-7% to compensate for the burning loss in the smelting process.
4. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that Step 2: ultrasonically clean the raw material using anhydrous ethanol.
5. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that The anti-oxidation coating in step 3 is TB1030 glass powder.
6. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that Step 4: Use a resistance heat treatment furnace for treatment.
7. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that The material of the pressure head used in step 5 is nickel-based high-temperature alloy.
8. The method for preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that Step 5: Monitor the temperature change during the compression process in real time through a thermocouple to control the temperature fluctuation during the compression process to be less than ±10°C.
9. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that Step 5: Control the compression amount to 50% to 80%.
10. The method of preparing a high-strength β titanium alloy having a two-phase mixed ultrafine grain structure by medium-temperature constant load deformation according to claim 1, characterized in that The high-strength β titanium alloy with a two-phase mixed ultrafine grain structure obtained in step 5 has an ultrafine grain structure mixed with α phase and β phase, and the grain size is less than 1 μm.
Citation Information
Patent Citations
Beta titanium alloy and preparation method thereof
CN101886189A
Ultrahigh-strength titanium alloy and preparation method thereof
CN103276242A
High-strength high-plasticity hot-strength titanium alloy wire material and processing and manufacturing method and application thereof
CN110983104A
Method for improving grain size and orientation distribution uniformity of high-temperature titanium alloy forging stock
CN115627430A
Creep forming / short-time heat treatment composite preparation method of high-niobium TiAl alloy with fine full lamellar structure
CN117089790A
